Long-term trends in smoking prevalence and its socioeconomic inequalities in Korea, 1992-2016 - Youngs Chang; Hee-Yeon Kang; Dohee Lim; Hong-Jun Cho; Young-Ho Khang (BMC, 2019)
Abstract Background The aim of this study was to investigate long-term trends in smoking prevalence and its socioeconomic inequalities in Korea. Methods Data were collected from 10 rounds of the Social Survey of Statistics Korea between 1992 and 2016. A total of 524,866 men and women aged 19 or over were analyzed. Age-adjusted smoking prevalence was calculated according to three major socioeconomic position indicators: education, occupational class, and income. The prevalence difference, prevalence ratio, slope index of inequality (SII), and relative index of inequality (RII) were calculated to examine the magnitude of inequality in smoking. Results Smoking prevalence among men decreased from 71.7% in 1992 to 39.7% in 2016, while smoking prevalence among women decreased from 6.5% in 1992 to 3.3% in 2016. Socioeconomic inequalities in smoking prevalence according to the three socioeconomic position indicators were found in both men and women throughout the study period. In general, absolute and relative socioeconomic inequalities in smoking, measured by prevalence difference and prevalence ratio for education and occupational class, widened during the study period among Korean men and women. In men, the SII for income increased from 7.6% in 1999 to 10.8% in 2016 and the RII for income also increased from 1.11 in 1999 to 1.31 in 2016. In women, the SII for income increased from 0.1% in 1999 to 2.4% in 2016 and the RII for income increased from 1.39 in 1999 to 2.25 in 2016. Conclusion Pro-rich socioeconomic inequalities in smoking prevalence were found in men and women. Socioeconomic inequalities in smoking have increased in parallel with the implementation of tobacco control policies. Tobacco control policies should be developed to decrease socioeconomic inequalities in cigarette use in Korea.